Air pollution co-benefits of low carbon policies in road transport: a sub-national assessment for India. (12th August 2015) - Mittal, Shivika; Hanaoka, Tatsuya; Shukla, Priyadarshi R; Masui, Toshihiko
Abstract: This letter assesses low carbon scenarios for India at the subnational level in the passenger road transport sector. We estimate the future passenger mobility demand and assess the impact of carbon mitigation policies using the Asia–Pacific Integrated Assessment/Enduse models. This letter focuses on the transitions of energy and emissions of passenger transport in India in alternate scenarios i.e. the business-as-usual scenario and a low carbon scenario that aligns to the 2 °C temperature stabilization target agreed under the global climate change negotiations. The modelling results show that passenger mobility demand will rise in all sub-national regions of India in the coming few decades. However, the volume and modal structure will vary across regions. Modelling assessment results show that aligning global low carbon policies with local policies has potential to deliver significant air quality co-benefits. This analysis provides insights into the comparative dynamics of environmental policymaking at sub-national levels.